Lithiophilic MXene‐Guided Lithium Metal Nucleation and Growth Behavior (Adv. Funct. Mater. 32/2021). (10th August 2021) - Ha, Son; Kim, Daesin; Lim, Hyung‐Kyu; Koo, Chong Min; Kim, Seon Joon; Yun, Young Soo
Abstract : Lithium Metal Batteries In article number 2101261, Seon Joon Kim, Young Soo Yun, and co‐workers study lithiophilic surface‐guided lithium metal nucleation and growth behaviors using a large‐area Ti3 C2 T x MXene electrode containing a large number of oxygen and fluorine dual heteroatoms. The lithiophilic MXene substrate significantly affects the surface tension of the lithium metal nuclei as well as the nucleation overpotential, forming highly reversible metal clusters composed of spherical lithium nanoparticles.